Spatial-temporal variation characteristics of air pollution and apportionment of contributions by different sources in Shanxi province of China. (1st January 2021) - Bai, Xiaoxuan; Tian, Hezhong; Liu, Xiangyang; Wu, Bobo; Liu, Shuhan; Hao, Yan; Luo, Lining; Liu, Wei; Zhao, Shuang; Lin, Shumin; Hao, Jiming; Guo, Zhihui; et al.
Abstract: With the implementation of the Air Pollution Prevention and Control Action Plan (APPCAP) since 2013, significant declines in pollutants concentrations have achieved in nationwide of China. However, as one of the major coal-production bases and intensive energy-consuming provinces in China, Shanxi has still been suffering from severe air quality problems in recent years. In this study, by combining a detailed bottom-up emission inventory and the weather research and forecasting (WRF) model/comprehensive air quality model with extensions (CAMx) model, the evolution of pollutant concentrations, source apportionment, and migration potentials from 2012 to 2015 in Shanxi are investigated. Estimated primary air pollutants emission declined significantly during 2012–2015. Compared with 2012, the simulated concentrations of PM2.5, PM10, SO2 and NO2 in January of 2015 are reduced by 24.7%, 24.1%, 23.0% and 18.0%, respectively. In contrast, heavy contaminated areas have shown negligible variations, which are highly concentrated in Taiyuan, Linfen, Jincheng, Changzhi, Lvliang, Yangquan and Jinzhong cities. In terms of contribution by source categories, the other industries and residential sources are identified as the most significant local contributors for PM2.5 and PM10, while SO2 and NO2 are mainly emitted by other industries and power plants. Scenarios analysis of 50% emission mitigation suggests that the emission reduction measures are generally more effective in summer than in winter. Moreover, the mitigation potential for each city varies from each other. These results indicate that more appropriate seasonal-specific emission reduction measures in each prefecture-level city should be implemented to further improve regional air quality and thus better protect public health. Graphical abstract: Image 1 Highlights: The first overall estimation of air pollution evolution in Shanxi is presented. Spatial-temporal pollution characteristics are investigated by WRF-CAMx model. Heavy contaminated areas have shown negligible variations from 2012 to 2015. Industries, residential, and power plants are main local pollution contributors. Mitigation potential for each city varies each other and more effective in summer.